The Mediating Effect of Perceived Institutional Support on Inclusive Leadership and Academic Loyalty in Higher Education - Gbobaniyi O.; Srivastava S.; Oyetunji A.K.; Amaechi C.V.; Beddu S.B.; Ankita B. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Globally, people have a rising desire to obtain certificates, degrees, and diplomas in higher institutions, described as diploma disease. Additionally, the need for sustainable education becomes imperative as globalization increases. To meet these demands, there is a need for Higher Education Institutions (HEIs) to have adequate support for both students and academics. However, these HEIs are faced with the challenge of meeting set goals and values. For leaders in HEIs, inclusion is a critical challenge. This paper investigates perceived institutional supports (PIS) role in mediating the co-relationship between academic loyalty and inclusive leadership within HEIs. The study presents a literature review to give some background. This papers conceptual framework is built on PIS from social exchange theories. Based on the design, a quantitative survey was adopted for the study. A random sample of 402 academics in HEIs was deployed for the study. A questionnaire instrument was designed to elicit information from the respondents. A structural equation model (SEM) was then adopted for the data analysis. The SEM approach was utilized to investigate the connection between academic loyalty and inclusive leadership at HEIs, with the mediating factor of PIS. The findings reveal a positive relationship exists between academic loyalty and inclusive leadership. While PIS positively connects both, there is also an inference that institutional support exists. This study provides insights that could assist stakeholders in formulating policies on employee needs and what could be done to improve and attain sustainable education in HEIs. It highlights applicable impacts towards increased productivity in HEIs, reflecting achieved targets regarding key performance indicators (KPI) and improved institutional performance. 2023 by the authors.